Stories of peoplehood: The politics and morals of political membership - Smith, Rogers M (Cambridge University, 2013)
How can we build thriving political communities? In this provocative account of how societies are bound together, Rogers Smith examines the importance of 'stories of peoplehood', narratives that promise economic of political power and define political allegiances in religious, cultural, racial, ethnic, and related terms. Smith argues that no nations are purely civic: all are bound in part by stories that seek to define elements intrinsic to their members' identities and worth. These types of stories can support valuable forms of political life but they also pose dangers that must be understood if they are to be confronted. In contrast to much contemporary writing, Stories of Peoplehood argues for community-building via robust contestation among sharply differing views. This original argument combines accessible theory with colourful examples of myths and stories from around the world and over 2,500 years of human history.